The Marital Violence under a gender view: domination and possibility of destruction of the hegemonily idealized model of marriage. - Rebeca Nunes Guedes; Ana Tereza Medeiros Cavalcanti da Silva; César Cavalcanti da Silva; Edméia de Almeida Cardoso Coelho; Waglânia de Mendonça Faustino e Freitas (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
This study is intended to enlarge the understanding of marital violence. In a qualitative analysis the research investigated what marital violence does mean to women victims of this kind of violence and how it affects their biological, emotional and social life. The results of the qualitative material in this research were achieved through interviews with women in situation of reported violence whose speeches were analyzed under the perspective of Fiorin 3. The analysis of the speeches showed that marital violence is a manifestation of the power assimmetry present in the relation of the genders and the women´s emotional feelings as well as their standard idealized profile as woman, wife and mother turned out to be a strong hidrance to their liberation from that violent relation and oppressive condition. The difficulty to face such a condition results in women having to go on living with their aggressors, which makes marital violence a recurrent, multifaceted phenomenon affecting their physical, mental and social health. Key words: Violence against women, gender and health, gender identity, power.